Ten Thousand Steps Per Day: To Follow Or Not? Is There Any Role of Technology? - Saurabh RamBihariLal Shrivastava; Nandkishor J. Bankar; Ankit K. Badge; Vaishnavi H. Mishra; Yugeshwari R. Tiwade; Gulshan R. Bandre (Wolters Kluwer Medknow Publications, 2024)
Noncommunicable diseases are universal and are being reported across the world, with many diseases being gradually reported in early age groups. Physical activity has been encouraged and advocated by all medical practitioners to prevent, arrest, and delay the onset and development of complications associated with noncommunicable diseases. The concept of "Ten Thousand Steps" in a day is predominantly a goal that people aim to attain either by walking or indulging themselves in some form of moderate physical activity. Since the inception of this concept, many health and fitness experts and public health agencies have recommended the same to achieve and maintain good health. Though there are numerous health-related benefits, people might encounter a wide range of challenges preventing them from attaining the goals consistently. In conclusion, the target of meeting ten thousand steps a day is much more than mere four-digit numbers, as a wide range of benefits have been attributed to the same. Although there are some challenges, the presence of technology and devices can help people continue with their active lifestyle, with fun and active engagement.